USE OF HERBAL PLANTS IN THE OFFER OF AGRITOURISM FARMS - Jaworska, Bożena (Polish Journal of Natural Sciences, 2024)
The aim of the study was to assess the activities of agritourism farms in the use of herbal plants. The basis for the assessment was an analysis of the agrotourism offer proposed in this respect on the websites of the surveyed farms. The offer of 25 agrotourism farms from different regions of Poland was analysed, which concerned the use of herbs in ornamental, utilitarian, cosmetic-therapeutic and educational aspects. The use of herbal plants in individual aspects varied considerably. All farms used herbs for ornamental and nutritional purposes. The use of herbs in the commercial and cosmetic-therapeutic aspects was on offer in every fourth farm. The educational aspect of the use of herbs was offered by three quarters of the farms. The educational offer was mostly carried out in the form of workshops. The topics of the classes varied. Most often, workshops were offered on learning about medicinal plants and their properties. Less frequently, workshops were offered on cooking, growing herbs, making herbal cosmetics and herbal therapies. The fewest workshops were offered on making herbal decorations. In general, the offer of using herbal plants in the activities of agritourism farms was well integrated into the agritourism context, and at the same time it fitted well into the cultural heritage of the Polish countryside.